2014
DOI: 10.1017/s0022149x14000650
|View full text |Cite
|
Sign up to set email alerts
|

Sequence variation in two mitochondrial DNA regions and internal transcribed spacer among isolates of the nematodeOesophagostomum asperumoriginating from goats in Hunan Province, China

Abstract: The present study examined sequence variability in two mitochondrial DNA (mtDNA) regions, namely cytochrome c oxidase subunit 1 (cox1) and NADH dehydrogenase subunit 1 (nad1), and internal transcribed spacer (ITS) of nuclear ribosomal DNA (rDNA) among Oesophagostomum asperum isolates from goats in Hunan Province, China. A portion of the cox1 (pcox1), nad1 (pnad1) genes and the ITS (ITS1+5.8S rDNA+ITS2) rDNA were amplified by polymerase chain reaction (PCR) separately from adult O. asperum individuals and the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
(40 reference statements)
4
3
0
Order By: Relevance
“…The phylogenetic tree showed the relationship with species Habronema sp. at an early evolutionary period, this is also similar to the another spirurida, confirming the results of the previous studies as" a typical marker for determining evolutionary history" (27), analysis of the phylogenetic among other species in relation to multiple branches within a monophyletic group. We determined the few substitutions of the related species in a family Habeonematidae depend on COX1 mtDNA gene, that related to a separate branch during an early evolutionary time; if reported the substitution number of 9-12/per local isolate (the substitution ratio about 1.98-2.6%)with H. muscae KX868085, then an increase in the mutations are reached 15.26% towards the early position according to the (Table 8),when comparing the substitution and identical ratios indicated for them in the results chapter between the local isolates both genes.…”
Section: Comparing the Genetic Markers In Identifying The Nematode P Skrjabinisupporting
confidence: 88%
See 3 more Smart Citations
“…The phylogenetic tree showed the relationship with species Habronema sp. at an early evolutionary period, this is also similar to the another spirurida, confirming the results of the previous studies as" a typical marker for determining evolutionary history" (27), analysis of the phylogenetic among other species in relation to multiple branches within a monophyletic group. We determined the few substitutions of the related species in a family Habeonematidae depend on COX1 mtDNA gene, that related to a separate branch during an early evolutionary time; if reported the substitution number of 9-12/per local isolate (the substitution ratio about 1.98-2.6%)with H. muscae KX868085, then an increase in the mutations are reached 15.26% towards the early position according to the (Table 8),when comparing the substitution and identical ratios indicated for them in the results chapter between the local isolates both genes.…”
Section: Comparing the Genetic Markers In Identifying The Nematode P Skrjabinisupporting
confidence: 88%
“…The multiple sequence alignment showed the a clear variation of ITS2rDNA region in P.skrjabini according to the sequences published in NCBI website, the mutation ratio reached 13.4% with Basra isolates taken from the small ruminants and the relatively less to the substitutions level has 8% of H. muscae (donkey) or P.smithi about 5.9% of early common ancestor, consequently, it is confirming the idea of P. skrjabini carries a unique pattern of the ITS2rDNA gene sequence. In the previous studies, the mitochondrial DNA variation within members of the same species was indicated 2-6% such as Ostertagia ostertagi (27). The mitochondrial DNA sequence of the related species range 10-20%; therefore, every two members may be a difference within 10% or more (27).…”
Section: Comparing the Genetic Markers In Identifying The Nematode P Skrjabinimentioning
confidence: 95%
See 2 more Smart Citations
“…When the study sequences were compared with reference sequences from China, Japan and Australia from BLAST search, sequence identities ranged from 97 to 100 % ( NCBI, 2022 ). Distinguished morphological characters of these two study species is proved by very high intra specific variation (19.5–20.1 %) between them which is supported by Hu et al, (2014) and Li et al, (2016) . Furthermore, slightly higher sequence diversity has also been reported by Jia et al, (2014) and Zhao et al, (2014) .…”
Section: Discussionsupporting
confidence: 73%